Noragami : Stray god, 13 - Adachi, Toka (Kodansha Comics, 2016)
Hiyori knows Kōto's real identity, and she's determined not to let him mess with her anymore. When he comes to pick on her again, she confronts him about Yato and refuses to back down. She's not afraid of him, but incurring the wrath of Yato's father comes with dire consequences